Groovy Eco Beats: Elevating Musical Intelligence in Preschoolers through Upcycled Drum Band Games - Ayunita, Siska; Zahra Lubis, Hilda; Hakim, Nurhaliza; SaÔÇÖadah Br BB, Nurul (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
This research aims to determine the improvement of musical intelligence in 5-6- year-old children through recycled drum band games. The research design used is classroom action research with a sample of 13 children selected through simple random sampling. Data collection techniques include observation, interviews, documentation, and the data obtained were analyzed using both quantitative and qualitative methods. The results of the research show that the musical intelligence of the children increased from cycle I to cycle 2 after the implementation of research and improvement actions. This indicates that recycled drum band games can enhance musical intelligence in 5-6-year-old children. The implementation of these activities is adjusted to the stages of their age, brain development, and intelligence. It involves introductory stages and methods that facilitate them in memorizing different beats in each played song.